Meat yield to total weight relationship in freshwater giant prawn Macrobrachium rosenbergii - Haq, M E; Quddus, M A (Indian Journal of Fisheries, 2011)
Information on the meat yield in relationto total weight in freshwater giant pmwnis important to both farmers and consumersin respect of marketing and processing aspects,but no report is available in this regard.The present study was undertaken todetermine the changes in the meat yield toincreasing total weight including carcasscomposition and length-weight relationshipof Macrobrachium rosenbergii.